Declining trends in smokeless tobacco use among Indian women: findings from global adult tobacco survey I and II - Shishirendu Ghosal (BMC, 2021)
Abstract Background Smokeless Tobacco (SLT) use is culturally rooted and more acceptable among women in India. SLT is a significant risk for oral cancers and has other adverse health outcomes on women’s general as well as reproductive health. This study aimed to estimate and compare the prevalence and correlates of SLT among adult females in India using Global Adult Tobacco Survey (GATS), 2009–2010 (GATS 1) and 2016–2017 (GATS 2). Methods Data from a nationally representative cross-sectional study GATS 1 (n = 35,529) and GATS 2 (n = 40,265) were analysed for adult female smokeless tobacco users. Correlates of SLT exposure were assessed separately using binary logistic regression. Multivariable logistic regression analysis was done for the variables which computed p < 0.1. The association was expressed as Adjusted Odds ratio with 95% confidence intervals. Results There was a reduction in prevalence of SLT use among women in India between GATS 1 (18.4%) and GATS 2 (12.8%). SLT use was highest among the North-Eastern women in both rounds [AOR: 4.567 (3.942–5.292) during GATS-1 and 9.149 (7.722–10.839) during GATS-2]. Odisha had highest prevalence of 56.53% while Himachal Pradesh had lowest 0.14% during the recent GATS 2 survey. 33.3% vs. 34.80% of the participants were willing to quit tobacco in Central region across both rounds of survey. Conclusions Although, smokeless tobacco prevalence among females has reduced between 2009 and 2016 in India, yet tobacco control strategies need further pace. Hence, more focused gender-based tobacco control programs and policies are the need of time.